RESEARCH ON THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF KINDERGARTEN TEACHERS - Shadiyeva, Shahnoza (Журнал иностранных языков и лингвистики, 2023)
Our article is primarily aimed at the substantive training and further education of preschool pedagogy, the training of fully qualified teachers, and the training and further education of specialists according to modern requirements. This article will consider some concepts and opinions of our scientists on the development of professional skills of preschool teachers based on authorship. Pedagogical skills are developed and improved during the work of each pedagogical staff, which of course depends on the work of a subject teacher. Currently, attention is paid to the development of the preschool education system in our country, a modern system created based on advanced foreign experience. Using modern pedagogical as well as information and communication technologies, the content of the preschool education system is researched and the most necessary foundations for its implementation are created.